A comparative evaluation of phytic acid as final rinse solution with other chelating agents for elimination of intraradicular smear: A scanning electron microscope study - Shrimanikandan Ayappa Gandhi; Preetha Chandrasekar; Jayaprakash Nachimuthu; Chris S Abraham; Karunakaran Jeyaraman Venkataraman (Wolters Kluwer Medknow Publications, 2020)
Aim: The aim of this study was to compare radicular smear layer removal ability of different solutions of phytic acid (PA) with other chelating agents when used in specific irrigant protocols. Materials and Methods: Seventy four maxillary central incisors were collected, standardized, and canals were prepared. A total of 5% sodium hypochlorite was used as the initial rinse solution (8 mL). Samples were divided into control (Group I-normal saline and II-7% ethylenediaminetetraacetic acid) and experimental groups (Group III, IV, V, VI, VII, and VIII) based on the type of final rinse solution used, that is, 5% PA, 10% PA, 17% PA, 5% citric acid (CA), 10% CA, and 17% CA (5 mL). Samples were coded, buccolingually divided into two halves, dehydrated, mounted, splutter coated, and examined under scanning electron microscope. Results: Group IV had the least smear and debris in coronal, middle, and apical thirds with mean scores of 1.06 and 1.3, respectively. When compared with Group II, no statistically significant difference was found (P > 0.05). Overall, the Group III had the lowest erosion scores at apical, middle, and coronal one-third with a mean of 1.68. Group VII had the highest amount of erosion with loss of peritubular and intertubular dentin at all levels. Conclusion: The role of PA as final rinse solution for the removal of radicular smear is promising and comparable to other chelating agents.